The World Health Organization - Connolly, Sean, 1956- (London : Franklin Watts, 2008)
Describes the history of efforts by the World Health Organization to ensure universal access to health care and to contain communicable diseases.
The health of the world -- Harnessing hope -- Real leadership -- First line of defense -- Global warning -- Rapid response -- Helping hands -- Looking ahead -- WHO and you.
Includes bibliographical references (p. 45) and index.
8.9
5-8
Keywords: World Health Organization -- Juvenile literature; World Health Organization; World Health Organization; Public health -- International cooperation -- Juvenile literature; World health -- Juvenile literature; Public health -- International cooperation; World health; Public health; Public health -- International cooperation